A subida do nível do mar durante o Holocénico no Golfo de Cadiz – tendência regional e diferenças locais - Moura, Delminda (2000)
In Guadiana River Estuary, the Holocene sequence is underlain by pebbly delta fan formed in two stages, prior to 5E and 3 highstands. The Holocene sedimentary sequence was lain either directly on gravels or on top of fluvial sands deposited between 11000 and 10000 yr. BP. An accelerated phase of infilling of the estuary by clayey sediments, containing marsh foraminifer Trochammina, began at ca. 9800 yr. BP when the sea level was about 39 m below the present.At ca. 7000 BP the central part of the estuary started to accommodate coarser sediments, partially introduced from the shelf. The first phase of the Holocene sea level rise at a rate of 0.85 m/century terminated at ca 6500yr. BP. Since then, the lagoonal bodies in the vicinity of estuary started to enclose behind sand spits and predominantly sandy sedimentation initiated within the estuary. After the second phase of a slower rise at the rate of 0.3 m/century, which lasted until ca. 5000 yr.BP, the sea approached the present level. Data from Guadalete Estuary published in Spain set the beginning of Holocene transgression at shallower level (ca 10m)than in Guadiana Estuary.This discrepancy may be explained by isostatic uplift of Betic Cordillera or slumping of Guadiana terrace on which the Holocene sediments are lain. Since 7500 yr. BP the data from Odiel-Tinto, Guadalete and Guadiana are in a relatively good agreement.